Lack of neutrophil elastase reduces inflammation, mucus hypersecretion, and emphysema, but not mucus obstruction, in mice with cystic fibrosis-like lung disease - Gehrig, Stefanie; Dürr, Julia; Weitnauer, Michael; Wagner, Claudius; Gräber, Simon Y.; Schatterny, Jolanthe; Hirtz, Stephanie; Belaaouaj, Abderrazzaq; Dalpke, Alexander; Schultz, Carsten; Mall, Marcus A. (American journal of respiratory and critical care medicine, 2014)
Rationale: Recent evidence from clinical studies suggests that neutrophil elastase (NE) released in neutrophilic airway inflammation is a key risk factor for the onset and progression of lung disease in young children with cystic fibrosis (CF). However, the role of NE in the complex in vivo pathogenesis of CF lung disease remains poorly understood.Objectives: To elucidate the role of NE in the development of key features of CF lung disease including airway inflammation, mucus hypersecretion, goblet cell metaplasia, bacterial infection, and structural lung damage in vivo.Methods: We used the Scnn1b-Tg mouse as a model of CF lung disease and determined effects of genetic deletion of NE (NE−/−) on the pulmonary phenotype. Furthermore, we used novel Foerster resonance energy transfer (FRET)-based NE reporter assays to assess NE activity in bronchoalveolar lavage from Scnn1b-Tg mice and sputum from patients with CF.Measurements and Main Results: Lack of NE significantly reduced airway neutrophilia, elevated mucin expression, goblet cell metaplasia, and distal airspace enlargement, but had no effect on airway mucus plugging, bacterial infection, or pulmonary mortality in Scnn1b-Tg mice. By using FRET reporters, we show that NE activity was elevated on the surface of airway neutrophils from Scnn1b-Tg mice and patients with CF.Conclusions: Our results suggest that NE plays an important role in the in vivo pathogenesis and may serve as a therapeutic target for inflammation, mucus hypersecretion, and structural lung damage and indicate that additional rehydration strategies may be required for effective treatment of airway mucus obstruction in CF.